Preservasi dan konservasi bahan pustaka cetak di perpustakaan universitas bojonegoro - Bagas Aldi Pratama; Novi Nur Ariyanti; Machsun Rifauddin (THE LIGHT : Journal of Librarianship and Information Science, 2025)
Libraries must carry out essential activities such as preservation and conservation, but in practice, various obstacles arise that prevent them from running smoothly. This study seeks to describe efforts to maintain and protect library items at the Bojonegoro University Library, as well as the challenges associated with carrying out these operations. This study employs descriptive research methodologies and a qualitative approach. Researchers analyzed data gathered through firsthand observations, interviews, and documentation. The Miles and Huberman model is used in the data analysis technique, namely for data reduction, data display, and conclusion drafting. Meanwhile, data veracity is checked using triangulation techniques. According to the study's findings, preservation and conservation actions such as binding, changing covers, re-covering, and digitalization media to the thesis collection were carried out at Bojonegoro University Library. Maintain cleanliness and control room humidity, supply plastic covers for all library materials. The issues encountered include a lack of facilities, room availability, a limited budget, and a shortage of human resources. Fumigation activities have never been carried out due to a lack of funds and qualified staff